The Effect of Green Accounting and Sustainability Report Disclosure on Firm Value in the Energy Sector - Sari, Mei Fantika; Hidayat, Rendra Arief (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2026)
This study aims to empirically analyze the effect of green accounting implementation and sustainability report disclosure on firm value, specifically focusing on energy sector entities listed on the Indonesia Stock Exchange (IDX) during the observation period of 2022 to 2024. The quantitative approach was employed by utilizing secondary data extracted from the companies' annual and sustainability reports. The research sample consists of 25 energy sector companies selected through a purposive sampling technique, resulting in 75 data observations over three years. Green accounting measurement is based on the GRI 300 environmental disclosure index, sustainability report disclosure is evaluated using the Sustainability Report Disclosure Index (SRDI), and firm value is projected using Tobin’s Q. The statistical results demonstrate that both green accounting and sustainability report disclosure have a positive and significant effect on firm value, both partially and simultaneously. These findings provide a strategic impact by recommending energy sector companies to substantively implement green accounting practices and transparency in sustainability reporting. This step is essential not only as a manifestation of environmental legitimacy but also as a fundamental strategy to enhance investor confidence and firm value amid the transition to a low-carbon economy.